Ionic liquid type catalyst for catalyzing chemical degradation reaction of polyurethane as well as preparation method and application of ionic liquid type catalyst

Through the design of ionic liquid catalysts, protonation of nitrogen heterocyclic compounds is used to form cations and anions, and the polyurethane is efficiently degraded under synergistic action, solving the problems of few catalyst types, low efficiency and metal ions interference in the prior art, and achieving low energy Consumable, efficient chemical degradation of polyurethane and efficient recycling of resources.

CN119143764APending Publication Date: 2024-12-17ZHEJIANG UNIV OF TECH

Patent Information

Application Number
CN202411143425.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-20
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

There are fewer types of polyurethane chemical degradation catalysts, low catalytic efficiency, and metal ions interfere with the preparation of recycled products, resulting in high reaction temperature, large energy consumption, large product molecular weight and high amine value, making it difficult to achieve efficient recycling of resources.

Method used

Using ionic liquid catalysts, the formation of cations and anions through protonation of nitrogen-containing heterocyclic compounds, promotes the activation of carbamate bonds and urea bonds in polyurethane, achieves efficient degradation under synergistic action, reduces reaction temperature, and increases reaction speed. Promote polyurethane preparation when product reuses.

Benefits of technology

It realizes a low volatility and low cost catalyst, reduces reaction temperature and energy consumption, improves catalytic efficiency, and the polyol properties of the product are close to the raw materials, which are suitable for efficient recycling and reuse of polyurethane materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143764A_ABST
    Figure CN119143764A_ABST
Patent Text Reader

Abstract

The invention discloses an ionic liquid type catalyst for catalyzing a polyurethane chemical degradation reaction and a preparation method and application thereof.The preparation method comprises the steps that a nitrogen-containing heterocyclic ring compound serves as a matrix and is dissolved in an organic solvent, the nitrogen-containing heterocyclic ring compound is protonized under the influence of acid, then separation and purification are conducted, and the ionic liquid type catalyst is formed; and then applying the ionic liquid type catalyst to a polyurethane chemical degradation reaction. The catalyst can efficiently catalyze various polyurethane chemical degradation reactions including acidolysis, alcoholysis, ammonolysis and alcohol aminolysis, and promotes the polyurethane preparation process when the product is recycled. Under the synergistic effect of cations and anions, the catalyst provided by the invention realizes more efficient treatment on polyurethane, and solves the problems that the existing polyurethane chemical degradation catalyst has fewer types, the catalytic efficiency and metal ions interfere with preparation of regenerated products and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polyurethane chemical degradation catalysts, and in particular to an ionic liquid catalyst for catalyzing polyurethane chemical degradation reactions, and a preparation method and application thereof. Background Art

[0002] Polyurethane is the sixth most common plastic in the world. Due to its excellent performance, it is widely used in smart home, automotive interior, aerospace and other fields. With the development of society, the amount and output of polyurethane foam in industry have increased year by year, and the amount of waste polyurethane products has also increased. Polyurethane is a kind of isocyanate and polyol [R-(OH) n≥2 ] Thermosetting polymers formed by polymerization and cross-linking cannot be recycled and reused by dissolving or melting. Polyurethane waste that is difficult to degrade can only be incinerated or landfilled, which will bring great waste of resources and environmental threats. At present, the chemical degradation and recycling methods of waste polyurethane mainly include alcoholysis, acidolysis, aminolysis, hydrolysis and enzymolysis, which can degrade polyurethane materials into polyurethane raw materials (such as polyols [R-(OH) n≥2 ]) or other chemical raw materials for recycling, thereby achieving the purpose of recycling resources and treating non-degradable waste. However, under mild conditions without a catalyst, the carbamate bond reacts slowly with the depolymerizer group, while the catalyst can reduce the reaction conditions to avoid thermal degradation, simplify the degradation mechanism, and at the same time improve the rate and degree of polyurethane depolymerization reaction. The Chinese invention patent application with publication number CN 107286369A discloses a method for acid-hydrolyzing polyurethane soft foam waste to generate polyols, in which polyols without amine compounds are obtained by acid hydrolysis. However, the degradation process temperature in the patent is relatively high (230-250°C), and it is difficult to avoid problems such as the volatilization of the acid hydrolyzer and the occurrence of side reactions; and the complete degradation process reaction time is relatively long (9-15h), the reaction process consumes a lot of energy, and the economic effect is poor. Therefore, the development of green and efficient chemical degradation and recovery technology for polyurethane materials and the establishment of an adapted catalyst system is a major research topic with innovative significance in the field of polyurethane.

[0003] In recent years, scholars have tried to design polyurethane degradation catalysts: Chinese patent application CN103374145A proposes to use a mixture of dihydroxy alcohol and ethanolamine as an alcoholysis agent, lithium acetate, sodium acetate or potassium acetate as a catalyst, and degrade the cast polyurethane elastomer at 145-195°C for a reaction time of 5.5-6.5h. Chinese patent application CN107955206A discloses a method for recycling polyether polyols by degradation of waste polyurethane foam, using small molecule alcohol as a degradation agent, metal hydroxide, metal acetate, and alcoholamine substances as catalysts to obtain reusable crude polyether polyols. It can be seen that the degradation schemes for waste polyurethane in the prior art are mainly alcoholysis or aminolysis, and most of them are assisted by metal catalysts or organic catalysts. The polyols obtained by these schemes are often large in molecular weight and high in amine value, and the operating space is small when they are reused. In summary, studying catalysts for polyurethane chemical degradation reactions and developing new catalyst systems to reduce reaction temperature, increase reaction speed, and improve product quality are one of the effective ways to solve this problem. Summary of the invention

[0004] In order to solve the problems of the limited types of existing polyurethane chemical degradation catalysts, catalytic efficiency, and metal ion interference in the preparation of regenerated products. The present invention proposes an ionic liquid catalyst for catalyzing polyurethane chemical degradation reactions, and its preparation method and application. The catalyst can efficiently catalyze a variety of polyurethane chemical degradation reactions including acidolysis, alcoholysis, aminolysis, and alcoholamine hydrolysis, and promote the polyurethane preparation process when the product is recycled. This ionic liquid can be dissociated into cations and anions when used, wherein the cation main body is a nucleophilic reagent, which can promote the activation of carbamate bonds and urea bonds in polyurethane and promote their rupture; and the ligand anion is an acidic group, which can activate the degradation agent used in the depolymerization reaction and increase the attack efficiency of the degradation agent. Under the synergistic effect of cations and anions, the catalyst of the present invention achieves more efficient degradation of polyurethane.

[0005] The key physical properties of the recycled polyols obtained by degradation and recycling through this method, such as hydroxyl value, acid value, amine value, viscosity, and water content, are basically the same as those of the raw polyols, and can partially replace the raw polyols to prepare polyurethane materials. In addition, the ionic liquid catalyst has the advantages of low volatility or non-volatility, and can maintain activity under reaction conditions, and can promote the reaction of the recycled polyols in the subsequent preparation process of polyurethane materials.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A preparation method and application of an ionic liquid catalyst for catalyzing a polyurethane chemical degradation reaction, wherein a nitrogen-containing heterocyclic compound is used as a matrix, dissolved in an organic solvent, and the nitrogen-containing heterocyclic compound is protonated under the influence of an acid, and then separated and purified to form the ionic liquid catalyst, which is then used in a polyurethane chemical degradation reaction.

[0008] A preparation step of an ionic liquid catalyst for catalyzing the chemical degradation reaction of waste polyurethane foam:

[0009] (1) Add an appropriate amount of methanol solution into a 100 ml three-necked flask, add one or more nitrogen heterocyclic compounds such as 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), 1,5-diazabicyclo[4.3.0]non-5-ene (DBN), 1,5,7-triazabicyclo[4.4.0]decene-5-ene (TBD), 1,4-diazabicyclo[2.2.2]octane (TED), 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene (MTBD), etc., dissolve the selected nitrogen heterocyclic compounds in methanol, and disperse them by ultrasonication.

[0010] (2) Add one or more of hydrochloric acid (HCl), sulfuric acid (H2SO4), nitric acid (HNO3), phosphoric acid (H3PO4), boric acid (H3BO3), formic acid (HCOOH), acetic acid (CH3COOH), benzoic acid (C7H6O2), methanesulfonic acid (CH4O3S), 1,3-diaza-2,4-cyclopentadiene (imidazole), diethyleneimine (pyrrole), diazacyclopentacyclic (pyrazole), azaindenebenzopyrrole (indole), etc. to a constant pressure dropping funnel, wherein the molar ratio of the acid used to the nitrogen heterocyclic compound used in step (1) is 1 to 2.2:1, and slowly add dropwise to the solution obtained in step (1) under nitrogen protection and constant temperature ice water bath conditions, with a dropping rate of 3 to 5 ml / min, preferably 4 ml / min, and a stirring speed of 200 to 500 rpm, preferably 300 rpm.

[0011] (3) After the dropwise addition is completed, the solution obtained in step (2) is placed at 20-30°C for reaction for 4-12 hours (preferably 8 hours).

[0012] (4) The reaction mixture obtained in step (3) is transferred to a 500 ml eggplant-shaped bottle, and subjected to rotary evaporation at 50-65° C. to remove excess raw materials and solvent. The product is taken out and placed in a culture dish, and the residual solvent is removed at 60° C. to obtain the ionic liquid catalyst.

[0013] The application of an ionic liquid catalyst for catalyzing the chemical degradation reaction of polyurethane in the chemical degradation reaction of polyurethane comprises: a degradation agent (acidolysis, alcoholysis, aminolysis, alcoholamine hydrolysis agent) and an ionic liquid catalyst for catalyzing the chemical degradation reaction of polyurethane are placed in a reactor, and then thermoplastic polyurethane elastomer particles are added to carry out chemical degradation reaction.

[0014] The gain effect of the present invention:

[0015] (1) The present invention expands the types of catalysts for chemical degradation of waste polyurethane foam by using a new type of ionic liquid catalyst. The method effectively solves the problems of harsh chemical degradation reaction conditions and high energy consumption, while also avoiding the problem that the use of metal ion catalysts is not conducive to the re-foaming of degradation products, providing a more efficient and lower-cost solution for large-scale industrial degradation of polyurethane foam.

[0016] (2) The ionic liquid catalyst used in the present invention is easy to prepare, easy to operate, low in cost, and convenient for industrial large-scale use.

[0017] (3) The method of the present invention uses a nitrogen heterocyclic organic catalyst and effectively improves the thermal stability and catalytic efficiency of the catalyst through ionization modification treatment.

[0018] (4) The ionic liquid catalyst used in the present invention can promote the nucleophilic addition reaction of the obtained product to form a carbamate bond when preparing a recycled polyurethane product. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 [TBDH prepared in Example 1 + ][Pyrazole - ]FTIR spectrum of ionic liquid catalyst.

[0020] Figure 2 This is a physical picture of the acid hydrolysis product of Example 1.

[0021] Figure 3 This is a physical picture of the regenerated product prepared from the polyol obtained by acid hydrolysis in Example 1.

[0022] Table 1 shows the mechanical properties of the regenerated product prepared from the polyol obtained by acid hydrolysis in Example 1.

[0023] Figure 4 [TBDH prepared in Example 2 + ][OAc - ]FTIR spectrum of ionic liquid catalyst.

[0024] Figure 5 This is a physical picture of the acidolysis product of Example 2.

[0025] Figure 6This is a physical picture of the polyether polyol separated and obtained in Example 2.

[0026] Figure 7 This is a physical picture of the regenerated product prepared from the polyol obtained by acid hydrolysis in Example 2.

[0027] Figure 8 This is a SEM image of the foam cells of the recycled product prepared from the polyol obtained by acid hydrolysis in Example 2.

[0028] Table 2 shows the mechanical properties of the recycled products prepared from the polyols obtained by acid hydrolysis in Example 2.

[0029] Fig. 9 [TBDH prepared in Example 3 + ][BA - ]FTIR spectrum of ionic liquid catalyst.

[0030] Fig.10 This is a physical picture of the acid hydrolysis product of Example 3.

[0031] Fig.11 This is a physical picture of the polyether polyol separated and obtained in Example 3.

[0032] Fig.12 This is a physical picture of the regenerated product prepared from the polyol obtained by acid hydrolysis in Example 3.

[0033] Fig.13 This is a SEM image of the foam cells of the recycled product prepared by acid hydrolysis of the polyol obtained in Example 3.

[0034] Table 3 shows the mechanical properties of the recycled products prepared from the polyol obtained by acid hydrolysis in Example 3.

[0035] Fig.14 [TBDH prepared in Example 4 + ][MSA - ]FTIR spectrum of ionic liquid catalyst.

[0036] Fig.15 This is a physical picture of the acidolysis product of Example 4.

[0037] Fig.16 This is a physical picture of the polyether polyol separated and obtained in Example 4.

[0038] Fig.17 This is a physical picture of the regenerated product prepared from the polyol obtained by acid hydrolysis in Example 4.

[0039] Fig.18 This is a SEM image of the pores of the recycled product prepared from the polyol obtained by acid hydrolysis in Example 4.

[0040] Table 4 shows the mechanical properties of the regenerated product prepared from the polyol obtained by acid hydrolysis in Example 4.

[0041] Fig.19 [TBDH prepared in Example 5 + ][HCOO - ]FTIR spectrum of ionic liquid catalyst.

[0042] Fig. 20 This is a physical picture of the acidolysis product of Example 5.

[0043] Fig.21 This is a physical picture of the polyether polyol separated in Example 5.

[0044] Fig. 22 This is a physical picture of the regenerated product prepared from the polyol obtained by acid hydrolysis in Example 5.

[0045] Fig.23 This is a SEM image of the pores of the recycled product prepared from the polyol obtained by acid hydrolysis in Example 5.

[0046] Table 5 shows the mechanical properties of the recycled products prepared from the polyol obtained by acid hydrolysis in Example 5.

[0047] Fig.24 [TBDH prepared in Example 6 + ][IM - ]FTIR spectrum of ionic liquid catalyst.

[0048] Fig.25 This is a physical picture of the polyester polyol separated in Example 6.

[0049] Fig.26 This is a physical picture of the regenerated product prepared from the polyol obtained by alcoholysis in Example 6.

[0050] Table 6 shows the mechanical properties of the recycled products prepared from the polyol obtained by alcoholysis in Example 6. DETAILED DESCRIPTION

[0051] The technical solution of the present invention is further described in detail below through specific embodiments in conjunction with the accompanying drawings.

[0052] Embodiment 1:

[0053] Add 50ml of methanol solution to a 100ml three-necked flask, add 13.9g (0.1mol) of 1,5,7-triazabicyclo[4.4.0]decene-5-ene (TBD), and disperse by ultrasonication for later use. Take 6.81g (0.1mol) of pyrazole and add it to the mixed solution of TBD and methanol. Set the stirring rate to 400rpm under nitrogen atmosphere and constant temperature ice water bath. After reacting at 25℃ for 8h, place the product in a 60℃ forced air oven to remove methanol to obtain [TBDH + ][Pyrazole - ], the mass is 20.53g, and the yield is 99.13%.

[0054]

[0055] In a 5L reactor equipped with mechanical stirring, heating temperature control and pressurizing devices, 500g of acidolysis agent and 5g of synthesized ionic liquid catalyst were added in a mass ratio of 100:1, and heated to 200°C, wherein the acidolysis agent was succinic acid and adipic acid in a mass ratio of 3:1, and the ionic liquid catalyst was [TBDH + ][Pyrazole - ], and its FT-IR spectrum is as follows Figure 1 As shown. The acidolysis agent and the catalyst are preheated, and 2 kg of crushed rigid polyurethane foam powder is added in a one-time addition, and the ratio of rigid polyurethane foam powder to the acidolysis agent is 4:1. After 1 hour of reaction, the rigid polyurethane foam powder completely disappears. After 3 hours of reaction, the basic physical properties of the degradation product have not changed significantly. The acid value is 0.2 mgKOH / g, the hydroxyl value is 185 mgKOH / g, the amine value is 0.2 mgKOH / g, the viscosity is 5000 mPa·s, the water content is 0.03%, and the color is black. After the product is allowed to stand and stratify, the upper layer is taken to obtain the recovered product polyether and polyester mixed polyols, and the lower layer is the polyamide compound obtained by degradation. The ratio of the upper and lower layers is 4:6 (such as Figure 2 When the recycled polyether-polyester mixed polyols replace the original polyols by 20 wt%, the mechanical properties of the recycled polyurethane foam can still meet the performance indicators of commercial polyurethane foam. Figure 3 Its mechanical properties are shown in Table 1.

[0056] Table 1

[0057]

[0058] Example 2

[0059] Add 50ml of methanol solution to a 100ml three-necked flask, add 13.9g (0.1mol) of 1,5,7-triazabicyclo[4.4.0]decene-5-ene (TBD), and disperse by ultrasonication for later use. Take 7.2g (0.12mol) of acetic acid (HOAc) and place it in a 50ml constant pressure dropping funnel. In a nitrogen atmosphere and a constant temperature ice water bath, slowly add it dropwise at a rate of 4ml / min to the dispersed mixed solution of TBD and methanol, and set the stirring rate to 300rpm. After reacting at 25℃ for 8h, place the product in a 60℃ forced air oven to remove methanol and excess acetic acid to obtain [TBDH + ][OAc - ], the mass is 19.3g, and the yield is 97.0%.

[0060]

[0061] In a 5L reactor equipped with mechanical stirring, heating temperature control and pressurizing devices, 400g of acidolysis agent and 4g of synthesized ionic liquid catalyst were added at a mass ratio of 100:1, and heated to 200°C, wherein the acidolysis agent was succinic acid and the ionic liquid catalyst was [TBDH + ][OAc - ], and its FT-IR spectrum is as follows Figure 4 As shown. The acidolysis agent and the catalyst were preheated, and 2 kg of crushed soft polyurethane foam was added in 30 minutes by continuous feeding method, and the ratio of soft polyurethane foam to acidolysis agent was 5:1. After 1.0 h of reaction, the rigid polyurethane foam powder completely disappeared. After 2.5 h of reaction, the basic physical properties of the degradation product had no obvious changes, the acid value was 0.2 mgKOH / g, the hydroxyl value was 58.5 mgKOH / g, the amine value was 0 mgKOH / g, the viscosity was 1000 mPa·s, the water content was 0.01%, and the color was light brown. After the product was allowed to stand and stratify, the upper layer was taken to obtain the recovered product polyether polyol, and the lower layer was the polyamide compound obtained by degradation. The ratio of the upper and lower layers was 1:1 (such as Figure 5 Use the recovered polyether polyol (such as Figure 6 When the recycled polyether polyol replaces the original polyol by 100 wt %, the mechanical properties of the recycled polyurethane foam can still meet the performance indicators of commercial polyurethane foam. Figure 7 As shown, its pore structure is as follows Figure 8 Its mechanical properties are shown in Table 2.

[0062] Table 2

[0063]

[0064] Example 3

[0065] Add 50ml of methanol solution to a 100ml three-necked flask, add 13.9g (0.1mol) of 1,5,7-triazabicyclo[4.4.0]decene-5-ene (TBD), and disperse by ultrasonication for later use. Take 12.2g (0.1mol) of benzoic acid (BA) and add it to the mixed solution of TBD and methanol. Under nitrogen atmosphere and constant temperature ice water bath, the stirring rate is set to 300rpm. After reacting at 25℃ for 12h, the product is placed in a 60℃ forced air oven to remove methanol to obtain [TBDH + ][BA - ], mass is 25.7g, yield is 98.5%.

[0066]

[0067] In a 5L reactor equipped with mechanical stirring, heating temperature control and pressurizing devices, 400g of acidolysis agent and 4g of synthesized ionic liquid catalyst were added at a mass ratio of 100:1, and heated to 200°C, wherein the acidolysis agent was succinic acid and the ionic liquid catalyst was [TBDH + ][BA - ], and its FT-IR spectrum is as follows Fig. 9 As shown. The acidolysis agent and the catalyst were preheated, and 2 kg of crushed soft polyurethane foam was added in 30 minutes by continuous feeding method, and the ratio of soft polyurethane foam to acidolysis agent was 5:1. After 1.5 hours of reaction, the rigid polyurethane foam powder completely disappeared. After 3 hours of reaction, the basic physical properties of the degradation product had no obvious changes. The acid value was 0.2 mgKOH / g, the hydroxyl value was 56.4 mgKOH / g, the amine value was 0.2 mgKOH / g, the viscosity was 1200 mPa·s, the water content was 0.02%, and the color was light brown. After the product was allowed to stand and stratify, the upper layer was taken to obtain the recovered product polyether polyol, and the lower layer was the polyamide compound obtained by degradation. The ratio of the upper and lower layers was 1:1 (such as Fig.10 Use the recovered polyether polyol (such as Fig.11 When the recycled polyether polyol replaces the original polyol by 70 wt %, the mechanical properties of the recycled polyurethane foam can still meet the performance indicators of commercial polyurethane foam. Fig.12 As shown, its pore structure is as follows Fig.13 Its mechanical properties are shown in Table 3.

[0068] Table 3

[0069]

[0070] Example 4

[0071] Add 50ml of methanol solution to a 100ml three-necked flask, add 13.9g (0.1mol) of 1,5,7-triazabicyclo[4.4.0]decene-5-ene (TBD), and disperse by ultrasonication for later use. Take 9.61g (0.1mol) of methanesulfonic acid (MSA) and add it to the mixed solution of TBD and methanol. Under nitrogen atmosphere and constant temperature ice water bath, the stirring rate is set to 400rpm. After reacting at 25℃ for 12h, the product is placed in a 60℃ forced air oven to remove methanol to obtain [TBDH + ][MSA - ], the mass is 23.3g, and the yield is 99.1%.

[0072]

[0073] In a 5L reactor equipped with mechanical stirring, heating temperature control and pressurizing devices, 400g of acidolysis agent and 4g of synthesized ionic liquid catalyst were added at a mass ratio of 100:1, and heated to 200°C, wherein the acidolysis agent was succinic acid and the ionic liquid catalyst was [TBDH + ][MSA - ], and its FT-IR spectrum is as follows Fig.14 As shown. The acidolysis agent and the catalyst were preheated, and 2 kg of crushed soft polyurethane foam was added in 30 minutes by continuous feeding method, and the ratio of soft polyurethane foam to acidolysis agent was 5:1. After 1.5 hours of reaction, the rigid polyurethane foam powder completely disappeared. After 3 hours of reaction, the basic physical properties of the degradation product had no obvious changes. The acid value was 0.2 mgKOH / g, the hydroxyl value was 54.5 mgKOH / g, the amine value was 0.1 mgKOH / g, the viscosity was 1100 mPa·s, the water content was 0.02%, and the color was light brown. After the product was allowed to stand and stratify, the upper layer was taken to obtain the recovered product polyether polyol, and the lower layer was the polyamide compound obtained by degradation. The ratio of the upper and lower layers was 1:1 (such as Fig.15 Use the recovered polyether polyol (such as Fig.16 When the recycled polyether polyol replaces the original polyol by 75 wt %, the mechanical properties of the recycled polyurethane foam can still meet the performance indicators of commercial polyurethane foam. Fig.17 As shown, its pore structure is as follows Fig.18 Its mechanical properties are shown in Table 4.

[0074] Table 4

[0075]

[0076] Example 5

[0077] Add 50ml of methanol solution to a 100ml three-necked flask, add 13.9g (0.1mol) of 1,5,7-triazabicyclo[4.4.0]decene-5-ene (TBD), and disperse by ultrasonication for later use. Take 5.52g (0.12mol) of formic acid (HCOOH) and place it in a 50ml constant pressure dropping funnel. In a nitrogen atmosphere and a constant temperature ice water bath, slowly add it dropwise at a rate of 4ml / min to the dispersed mixed solution of TBD and methanol, and set the stirring rate to 300rpm. After reacting at 25℃ for 6h, place the product in a 60℃ forced air oven to remove methanol and excess formic acid to obtain [TBDH + ][HCOO - ], the mass is 18.3g, and the yield is 98.9%.

[0078]

[0079] In a 5L reactor equipped with mechanical stirring, heating temperature control and pressurizing devices, 400g of acidolysis agent and 4g of synthesized ionic liquid catalyst were added at a mass ratio of 100:1, and heated to 200°C, wherein the acidolysis agent was succinic acid and the ionic liquid catalyst was [TBDH + ][HCOO - ], and its FT-IR spectrum is as follows Fig.19 As shown. The acidolysis agent and the catalyst were preheated, and 2 kg of crushed soft polyurethane foam was added in 30 minutes by continuous feeding method, and the ratio of soft polyurethane foam to acidolysis agent was 5:1. After 1.5 hours of reaction, the rigid polyurethane foam powder completely disappeared. After 3 hours of reaction, the basic physical properties of the degradation product had no obvious changes. The acid value was 0.4 mgKOH / g, the hydroxyl value was 52.5 mgKOH / g, the amine value was 0.1 mgKOH / g, the viscosity was 1300 mPa·s, the water content was 0.03%, and the color was light brown. After the product was allowed to stand and stratify, the upper layer was taken to obtain the recovered product polyether polyol, and the lower layer was the polyamide compound obtained by degradation. The ratio of the upper and lower layers was 1:1 (such as Fig. 20 Use the recovered polyether polyol (such as Fig.21 When the recycled polyether polyol replaces the original polyol by 80 wt%, the mechanical properties of the recycled polyurethane foam can still meet the performance indicators of commercial polyurethane foam. Fig. 22 As shown, its pore structure is as follows Fig.23 Its mechanical properties are shown in Table 5.

[0080] Table 5

[0081]

[0082] Example 6

[0083] Add 50ml of methanol solution to a 100ml three-necked flask, add 13.9g (0.1mol) of 1,5,7-triazabicyclo[4.4.0]decene-5-ene (TBD), and disperse by ultrasonication for later use. Take 6.8g (0.1mol) of imidazole (IM) and add it to the mixed solution of TBD and methanol. Under nitrogen atmosphere and constant temperature ice water bath, the stirring rate is set to 400rpm. After reacting at 25℃ for 12h, the product is placed in a 60℃ forced air oven to remove methanol to obtain [TBDH + ][IM - ], the mass is 20.3g, and the yield is 98.1%.

[0084]

[0085] In a 5L reactor equipped with mechanical stirring, heating temperature control and pressurizing devices, 200g of alcoholysis agent and 2g of synthesized ionic liquid catalyst were added in a mass ratio of 100:1 and heated to 150°C, wherein the alcoholysis agent was ethylene glycol and the ionic liquid catalyst was [TBDH + ][IM - ], and its FT-IR spectrum is as follows Fig.24 As shown, the alcoholysis agent and catalyst are preheated, and 2 kg of thermoplastic polyurethane elastomer particles are added by a one-time feeding method. The ratio of thermoplastic polyurethane elastomer particles to alcoholysis agent is 10:1. After 1.0 h of reaction, the thermoplastic polyurethane elastomer particles completely disappeared. After 3 h of reaction, the basic physical properties of the degradation product had no obvious changes. The excess degradation agent was separated by rotary evaporation to obtain the product polyester polyol. The hydroxyl value is 220.5 mgKOH / g, the amine value is 0.1 mgKOH / g, the viscosity is 2000 mPa·s, the water content is 0.02%, and the color is light yellow. The obtained polyester polyol (such as Fig.25 As shown in the figure, the recycled polyester polyol is used to prepare thermoplastic polyurethane elastomer. When the recycled polyester polyol replaces the original polyol by 50wt%, the mechanical properties of the recycled thermoplastic polyurethane elastomer can still meet the performance indicators of commercial thermoplastic polyurethane elastomer. Fig.26 Its mechanical properties are shown in Table 6.

[0086] Table 6

[0087]

[0088] Comparative Example 1

[0089] In a 5L reactor equipped with mechanical stirring, heating temperature control and pressurizing devices, add 500g of acidolysis agent and heat to 200℃, wherein the acidolysis agent is succinic acid and adipic acid, with a mass ratio of 3:1. Preheat the acidolysis agent, add 2kg of crushed rigid polyurethane foam powder in a one-time addition, and the ratio of rigid polyurethane foam powder to acidolysis agent is 4:1. After reacting for 1h, the rigid polyurethane foam powder completely disappears. After reacting for 3h, the rigid polyurethane foam powder degrades, with an acid value of 20mgKOH / g, a hydroxyl value of 85mgKOH / g, and a viscosity of>10 5 mPa·s, dark brown in color.

[0090] Comparative Example 2

[0091] In a 5L reactor equipped with mechanical stirring, heating temperature control and pressurizing devices, 400g of acidolysis agent was added and heated to 200℃, wherein the acidolysis agent was succinic acid. The acidolysis agent was preheated, and 2kg of crushed soft polyurethane foam was added in 30min by continuous feeding method, and the ratio of soft polyurethane foam to acidolysis agent was 5:1. After 1.5h of reaction, the rigid polyurethane foam powder completely disappeared. After 5h of reaction, the basic physical properties of the degradation product had no obvious changes, the acid value was 8.4mgKOH / g, the hydroxyl value was 32.5mgKOH / g, the amine value was 0.4mgKOH / g, the viscosity was 20000mPa·s, the water content was 0.03%, and the color was light brown.

[0092] Comparative Example 3

[0093] In a 5L reactor equipped with mechanical stirring, heating temperature control and pressurizing device, 200g of alcoholysis agent was added and heated to 150℃, wherein the alcoholysis agent was ethylene glycol. The alcoholysis agent was preheated, and 2kg of thermoplastic polyurethane elastomer particles were added by a one-time feeding method. The ratio of thermoplastic polyurethane elastomer particles to alcoholysis agent was 10:1. When the reaction lasted for 1.0h, the thermoplastic polyurethane elastomer particles did not completely disappear. When the reaction lasted for 5h, the basic physical properties of the degradation product had no obvious changes. The excess degradation agent was separated by rotary evaporation to obtain the product polyester polyol. The hydroxyl value was 160.5mgKOH / g, the amine value was 0.4mgKOH / g, the viscosity was 3500mPa·s, the water content was 0.03%, and the color was light yellow.

[0094] Comparative Example 4

[0095] In a 5L reactor equipped with mechanical stirring, heating temperature control and pressurizing devices, 200g of degradation agent was added and heated to 180°C, wherein the degradation agent was diethanolamine and the diluent was polyether polyol 5616. The degradation agent, catalyst and diluent were preheated, and 2kg of crushed soft polyurethane foam was added by continuous feeding method, and the ratio of soft polyurethane foam to degradation agent was 10:1. When the reaction lasted for 2.0h, the soft polyurethane foam completely disappeared. When the reaction lasted for 6h, the basic physical properties of the degradation product had no obvious changes, and the product polyether polyol was obtained. The hydroxyl value was 57mgKOH / g, the amine value was 0.3mgKOH / g, the viscosity was 5000mPa·s, the water content was 0.03%, and the color was light yellow.

Claims

1. A method for preparing an ionic liquid catalyst for catalyzing the chemical degradation reaction of polyurethane, characterized in that: The following steps are involved: (1) dissolving the nitrogen heterocyclic compound in methanol and performing ultrasonic dispersion to obtain a nitrogen heterocyclic compound solution; (2) adding a protonating agent to the nitrogen heterocyclic compound solution; (3) placing the solution obtained in step (2) at 20 to 30° C. for a reaction of 4 to 12 hours; (4) The reaction mixture obtained in step (3) is post-treated to obtain an ionic liquid catalyst.

2. The preparation method according to claim 1, characterized in that: In step (1), the nitrogen heterocyclic compound is one or more of 1,8-diazabicyclo[5.4.0]undec-7-ene, 1,5-diazabicyclo[4.3.0]non-5-ene, 1,5,7-triazabicyclo[4.4.0]decene-5-ene, 1,4-diazabicyclo[2.2.2]octane, and 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene.

3. The preparation method according to claim 1, characterized in that: In step (2), the protonating agent is one or more of hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, boric acid, formic acid, acetic acid, benzoic acid, methanesulfonic acid, 1,3-diaza-2,4-cyclopentadiene, diethyleneimine, diazacyclopentadiene, and azaindenebenzopyrrole.

4. The preparation method according to claim 1, characterized in that: The molar ratio of the protonating agent in step (2) to the nitrogen heterocyclic compound in step (1) is 1 to 2.2:

1.

5. The preparation method according to claim 1, characterized in that: In step (2), the protonating agent is added under nitrogen protection and a constant temperature ice-water bath.

6. The preparation method according to claim 1, characterized in that: In step (4), the post-treatment includes: performing a rotary evaporation operation at 50-65° C. to remove excess raw materials and solvent.

7. The preparation method according to claim 1, characterized in that: In step (4), the ionic liquid catalyst is one or more of the following structures:

8. An ionic liquid catalyst for catalyzing the chemical degradation reaction of polyurethane prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the ionic liquid catalyst for catalyzing the chemical degradation reaction of polyurethane according to claim 8 in the chemical degradation reaction of polyurethane.

10. The use according to claim 9, characterized in that: include: In the reactor, a degradation agent and an ionic liquid catalyst for catalyzing the chemical degradation reaction of polyurethane are added, and then thermoplastic polyurethane elastomer particles are added to carry out chemical degradation reaction.

Citation Information

Patent Citations

  • Recovery process of polyurethane waste

    CN103374145A

  • Method for acidolysis of soft polyurethane foam waste to produce polyol

    CN107286369A

  • Method for degrading waste polyurethane foam to recycle polyether polyol

    CN107955206A

Cited By

  • Method for catalytically degrading polyester material by using ionic liquid and application

    CN121045642A

  • A composite catalyst and its use for the one-step preparation of high purity DMT or BHET

    CN122895046A